Protomelas krampus, a new paedophagous cichlid from Lake Malawi (Teleostei, Cichlidae) - Dierickx, Katrien; Snoeks, Jos (European Journal of Taxonomy, 2020)
A new paedophagous species of Protomelas, P. krampus sp. nov., is described from Lake Malawi. It has been found in Lukoma Bay in Tanzania, near Mara Point in Mozambique, and at Otter Point, Chizumulu, the Likoma Islands and Mazinzi Reef in Malawi. This species is placed in the genus Protomelas based on its melanin pattern, which comprises a continuous midlateral stripe. A morphometric study was done to compare this species with its congeners and similar species of Hemitaeniochromis and Caprichromis. It differs from most congeners by having only one inner tooth row. Furthermore, P. krampus sp. nov. differs from P. insignis, P. spilopterus, H. brachyrhynchus, H. urotaenia, Caprichromis liemi and C. orthognathus by its shorter premaxillary pedicel, shorter prepectoral distances and dentition. It also differs largely in its melanin pattern from the paedophagous species C. liemi, C. orthognathus, Diplotaxodon greenwoodi and Naevochromis chrysogaster, as well as H. brachyrhynchus and H. urotaenia. Protomelas krampus sp. nov. has been observed to ram mouth-brooding cichlids from above to feed on their eggs or larvae.